Postgraduate evaluation results through distance education during COVID-19 - Ana Caridad López Vantour; Maurin Castelnaux Martínez; Maritza del Carmen Berenguer Gouarnaluses (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: The implementation of the education at distance during the process of teaching learning of the posgrado in the current context of the pandemic COVID-19, constitutes an alternative from the system of superior education to world level. Objective: to describe the results obtained in the Module 7 Attention to the smaller than 19 years I, by means of the education modality at distance during the third rebrote of the Pandemic of COVID -19. Methods: he/she was carried out a descriptive traverse observational study between June and July of 2021, in the Ability of Estomatología of the University of Medical Sciences of Santiago from Cuba. They were considered as analysis units: didactic units, students (residents), a random sample was selected (n = 96). The variables results of the evaluations of each didactic and general unit of the module (excellent, well, regular and bad), grade of difficulty (very difficult, difficult and without difficulty) and level of satisfaction (satisfied, fairly satisfied and unsatisfied) were studied. As mensuration instrument evaluation registration was used and of interview, respectively. It was used the percentage like summary measure. Results: more than 50% of the evaluated residents it was in the category of well without any difficulty, being satisfied with the education modality at distance employee. Conclusions: the implementation of the education at distance during the sanitary current situation in the specialty of EGI is an opportunity to develop the educational process in the posgrado.